Compressible Flow of Air in Non Circular Ducts - Bengtson, Harlan (McGraw-Hill's AccessEngineering., 2015)
Calculations for adiabatic, compressible flow (Fanno Flow) of air in non-circular ducts are very time-consuming as they require multiple levels of difficult calculations using tables and iterative solutions. This Excel workbook streamlines these calculations by automating the iterative calculation of the friction factor and the overlaying iterative solution of the Fanno Flow equations. Worksheets are included to calculate frictional pressure drop (for specified flow rate) and to calculate flow rate (for specified pressure drop) for each of three duct configurations: circular annulus, rectangular and other non-circular shapes. Each of the worksheets includes calculation of choked flow conditions and incompressible flow calculations in addition to calculation of the unknown parameter using the appropriate Fanno Flow equations.